Attachment Styles, Personality Organization, and Substance Use as Predictors of Emotion Regulation Strategies “Suppression” and “Reappraisal” in Young Adults - Burgkart, Pauline L.; Vuzic, Xenia; Fuchshuber, Jürgen; Unterrainer, Human-Friedrich (Frontiers in Psychiatry, 2022)
Background: As evidenced by current literature there is a crucial link between emotion regulation, attachment, personality patterns and substance abuse. However, knowledge regarding the exact interactions of these specific parameters in terms of substance abuse development is still sparse. Therefore, this study is aimed to shed light on how two specific emotion regulation strategies (“Reappraisal” and “Suppression”) might be influenced by the relationship between attachment, structural deficits in personality organization and addictive behaviors. Method: A total sample of 299 nonclinical young adults (Age: M = 22; SD = 3.81; 74.2 % females) filled in the Emotion Regulation Questionnaire (ERQ) together with the Adult Attachment Scale (AAS), the Personality Organization Inventory (IPO-16) and the Alcohol, Smoking and Substance Involvement Screening (ASSIST) by means of an online survey. Results: As suggested by hierarchical regression analysis, attachment specifically predicted differences in Emotion Regulation (ER), whereby the AAS sub-scales “Close”ness (β= -0.38, p< 0.01), and “Depend”ence (β= -0.18, p< 0.01) were negatively associated with increased use of maladaptive strategies of expressional suppression of emotion, and “Depend” (β= 0.26, p< 0.01) was positively associated with increased use of adaptive strategies of cognitive reappraisal. Discussion: In line with our assumptions, we observed a more secure attachment system to be predictive for an increased use of adequate emotion regulation strategies. The findings support the suggestion that a focus on underlying attachment-related processes in a psychotherapeutic setting might be a promising way to promote adaptive self-regulation of emotions.